(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article highlights the significance of body language in nonverbal communication. Body language refers to the use of nonverbal cues such as posture,gestures, facial expressions, and eye contact to convey messages and emotions. The article discusses the importance of body language in conveying emotions and attitudes more accurately than spoken language, and its role in building rapport and establishing trust. The article also explores the impact of cultural differences on body language interpretation and the need for individuals to be aware of these differences